Dark matter searches with cosmic-ray detectors and the Square Kilometre Array - Méndez, Isla Miguel Alfonso (Department of Maths and Applied Maths, 2020)
Beyond gravitational evidence for dark matter, a set of search techniques are employed in the present thesis within the particle dark matter paradigm. Under the possibility of dark matter annihilating into particles of the Standard Model of Particle Physics, we study the products of annihilation with cosmic-ray detectors, such as AMS, Fermi-LAT and PAMELA, and radio telescopes, such as the SKA. In this work, we focus on the positron fraction measured in the Solar System due to dark matter annihilating in the dark matter galactic halo, but also on radio signals from the Milky Way and dwarf spheroidal galaxies. Our main purpose is to constrain the dark matter parameter space under the light of the latest experimental data for cosmic-rays and the new sensitivities reached in radio astronomy. Furthermore, we discuss some of the most promising locations and synchrotron frequencies to search for dark matter with masses around the TeV scale. The analysis presented in this thesis lies in setting constraints on modelindependent dark matter. However, some specific dark matter candidates in the context of extra-dimensional theories are considered as well. Indeed, brane fluctuations, dubbed branons, are new degrees of freedom appearing in flexible brane-world models. These new fields behave as standard weakly interacting massive particles with a significant associated thermal relic density and would explain dark matter observational features.